Microtoponymy in the Interlingual Space: Names of Vilnius Intracity Objects - Sinočkina, Birutė (Slavistica Vilnensis, 2022)
The article is devoted to the names of intracity topographical objects of the Lithuanian capital and their foreign language transmission. The subject of consideration are the official urbanonyms, used both to fix a specific place in the urban area, and performing a historical and educational function. Particular attention is paid to Lithuanian urbanonyms, the transfer of which into other languages ​​is associated with difficulties and is devoid of unambiguity. The specific speech material analyzed in the article includes Vilnius microtoponyms that have appeared or become relevant in recent times. The article outlines certain features of the practical Lithuanian−Russian transcription and contains recommendations for its application. Attention is also paid to the grammatical form of Russian words dating back to Lithuanian toponyms, as well as the specifics of syntactic constructions with these words. The choice of the method of transferring the original toponym in a foreign language in all cases is determined by the aim of maintaining a balance between the authenticity of the name, proximity to the Lithuanian original and the understandability of the name for a foreign user. The article is intended to contribute to streamlining the Lithuanian toponyms used in Lithuania and abroad in Russian transmission and is intended primarily for journalists, translators, editors who specialize in local topics and for guides.